Strategi Pemasaran Produk Kerupuk Tahu Bagus Hasby Berbasis Marketing Mix: Studi Kasus Umkm di Desa Buah Berak - Viola De Yusa; Betty Magdalena; Riyadini Riyan Utami (Pusat Studi Teknologi Informasi Fakultas Ilmu Komputer Universitas Bandar Lampung, 2026)
Buah Berak Village, located in Kalianda District, South Lampung Regency, has significant economic potential, particularly in the micro, small, and medium enterprises (MSMEs) sector. One of the developing MSMEs is Kerupuk Tahu Bagus Hasby. However, the main challenges faced include limitations in marketing strategies, especially in digital marketing, product packaging, and financial recording. This community service activity aims to optimize MSME marketing strategies using the marketing mix (4P) approach: product, price, promotion, and place. The implementation method includes observation, interviews, mentoring, and the application of digital-based marketing strategies. The results show improvements in product quality through packaging enhancement, stable and competitive pricing, utilization of social media for promotion, and expansion of distribution channels. Additionally, MSME actors have increased their understanding of modern marketing strategies to enhance business competitiveness. Therefore, the implementation of the marketing mix has proven to have a positive and sustainable impact on the development of Kerupuk Tahu Bagus Hasby MSME.